Evaluation of palm oil sludge treatment by thermophilic anaerobic digestion - Chin, K. K.; Wong, K. K. (1981)
A laboratory study was undertaken to determine the feasibility of using a thermophilic anaerobic digestIon process to treat palm oil mill wastes. Raw wastewater contained 67,000 mg/l COD, 31,800 mg/l suspended solids with a pH of 4.5. Completely mixed reactors were operated to evaluate the effects of feed strength and solids retention times on the system's performance. A range of 5 to 35 day solids retention times was studied. Results indicated that increasing solids retention time improve'd digestion performance in term of COD and volatile solids removal. COD reduction was 72% for the 5 day detention time unit. More than 90% COD removal was achieved at detention times greater than 15 days. pH of all units was aelf adjusted to 7.4. Gas production was, in general, greater 3 than 0.3 m /kg volatile solids feed.